Synthesis and Antioxidant Properties of Novel 1,2,3-Triazole-Containing Nitrones - Dimitra Hadjipavlou-Litina; Iwona E. Głowacka; José Marco-Contelles; Dorota G. Piotrowska (MDPI AG, 2022)
Herein, we report the synthesis and antioxidant capacity of twelve novel 1,2,3-triazole-containing nitrones such as N-(2-(4-aryl-1H-1,2,3-triazol-1-yl)ethylidene)methanamine oxides 8a-f and N-(2-(4-aryl)-1H-1,2,3-triazol-1-yl)ethylidene)-2-methylpropan-2-amine oxides 9a-f, bearing an N-methyl, and an N-t-butyl substituent, respectively, at the nitrogen of the nitrone motif. Nitrones 8 and 9 were studied with regard to their antioxidant ability, as well as their ability to inhibit soybean lypoxygenase (LOX), and their in vitro antioxidant activity. For this, we used three different antioxidant assays, such as that featuring the interaction with the water-soluble azo compound AAPH for the inhibition of lipid peroxidation (LP), the competition with the DMSO for scavenging hydroxyl radicals, and the ABTS•+-decolorization assay. t-Butyl nitrone 9e, bearing the 2,4-difluorophenyl motif, showed a strong LP inhibitory effect (100%), close to the reference compound Trolox (93%), being the most potent LP inhibitor (LPi) of the whole series of tested nitrones. Nitrones 9d, 9e and 9f, bearing the 4-fluorophenyl, 2,4-difluorophenyl, and 4-fluoro-3-methylphenyl motif, respectively, were almost equipotent, and the most potent hydroxyl radical scavengers (~100%), more potent than Trolox (88%), were used as a reference compound. Regarding the LOX inhibition, the most potent inhibitor was the t-butyl substituted nitrone 9f (27 μM), bearing the 4-fluoro-3-methylphenyl motif, being 60-fold less potent than NDGA (0.45 μM), which was used as the standard in this test. The results from the antioxidant determination in the ABTS radical cation (ABTS•+) decolorization assay were not significant. N-Methyl nitrone 8f, bearing the 4-fluoro-3-methylphenyl motif, was the only promising representative, with a value of 34.3%, followed by nitrone 9f (16%). From the antioxidant analyses, we have identified N-(2-(4-(4-fluoro-3-methylphenyl)-1H-1,2,3-triazol-1-yl)ethylidene)-2-methylpropan-2-amine oxide (9f), bearing t-butyl and 4-fluoro-3-methylphenyl motifs in its structure, as the most balanced and potent antioxidant agent among the tested nitrones, as it was the most potent LOX inhibitor (27 μM), an extremely efficient and potent hydroxyl radical scavenger (99.9%), as well as one of the most potent LPi (87%) and ABTS•+ scavengers (16%).